Cisto dentígero em equino - relato de caso - Almeida, Laressa Marques (Universidade Federal Rural do Semi-Árido, 2019)
Atrial septal defect or dental cyst (CDT) is a condition resulting from abnormal consolidation of the first brachial cleft, occurring during embryonic development, or from non-eruption of the teeth, with detachment and migration of the dental follicle, resulting in ectopic access of odontoblastic cells in the cervicofacial area. The temporal region is where the deposit of these cells most occurs. Consists of a common fistulous condition, which presents a variable amount of dental elements, isolated or combined, and can be presented with molariform features. Diagnosis is obtained through clinical and complementary examinations, and the confirmation of the disease comes through histopathological examination. Clinical signs are usually subtle, and the animal may feel pain when submitted to palpation. The effective treatment consists in the surgical excision of all cystic complexes. The present report describes the care of a 13-monthold quarter-mile equine female patient, presenting an increase in the volume of the right temporal bone region, with the presence of fistula and draining a viscous fluid of mucopurulent characteristic.
Monografia
Keywords: Odontologia equina; Teratoma temporal; Polidontia heterotópica; Odontoma; Equine dentistry; Temporal teratoma; Heterotopic polydontia; Odontoma; CIENCIAS AGRARIAS::MEDICINA VETERINARIA